The effectiveness of BRADeR learning model to improve junior high school students' science literacy abilities - Aprido Simamora; Andriono Manalu; Rianita Simamora (Research and Development in Education (RaDEn), 2024)
The BRADeR learning model is an innovative model developed to help teachers train students' scientific literacy skills. The aim of this research is to determine the effectiveness of the BRADeR learning model in improving junior high school students' scientific literacy skills. This research is included in the type of quasi-experimental research. The research design used is quantitative research using descriptive methods (descriptive-quantitative). The subjects of this research were seventh class students at State Junior High School 5 of Pematangsiantar. Data collection techniques are in the form of tests, and the data analysis process uses descriptive quantitative-qualitative and n-gain. The results of the research show that the BRADeR learning model is effective, in terms of: a) its influence on the scientific literacy abilities of junior high school students, where: (1) n-gain in the scientific literacy abilities of junior high school students is in the medium to high category, and (2) there is an increase in literacy abilities science junior high school students. From the research results, it can be concluded that the BRADeR learning model is effective in improving junior high school students' scientific literacy skills. Other researchers can strengthen research in this area, expand its scope, and ensure that the learning models developed can be applied more effectively and are relevant to broader contexts.